CHAMP1 disorder is associated with a complex neurobehavioral phenotype including autism, ADHD, repetitive behaviors and sensory symptoms. Issue 15 (11th March 2022) - Levy, Tess; Lerman, Bonnie; Halpern, Danielle; Frank, Yitzchak; Layton, Christina; Zweifach, Jessica; Siper, Paige M; Buxbaum, Joseph D; Kolevzon, Alexander
Abstract: CHAMP1-related neurodevelopmental disorder, or CHAMP1 disorder, is a recently described genetic syndrome associated with developmental delay, intellectual disability, behavioral symptoms, medical comorbidities, and dysmorphic features. To date, literature has focused on medical review and dysmorphology but has yet to prospectively assess neurobehavioral core domains such as autism, or behavioral, language, cognitive, and sensory features. Here, we present deep phenotyping results for 11 individuals with CHAMP1 disorder, based on approximately 12 hours of remote clinician-administered assessments and standardized caregiver questionnaires. Diagnoses of autism spectrum disorder were given to 33% of participants; repetitive behaviors and sensory-seeking symptoms were prominent in this cohort. In addition, 60% of participants met the criteria for attention-deficit/hyperactivity disorder (ADHD). High rates of ADHD and relatively low rates of treatment suggest potential areas for intervention. This study represents the first prospective phenotyping analysis of individuals with CHAMP1 disorder. The utility of specific measures as clinical endpoints, as well as benefits and limitations of remote phenotyping, are described.